Pendidikan Kepesantrenan: Negosiasi Ruang Kaum Santri dalam Mempertahankan Identitas Sosial Keagamaan di Universitas Sains Al-Qur’an Wonosobo - Sakir, Moh.; El Syam, Robingun Suyud (LP. Ma'arif Janggan Magetan, 2024)
This research seeks to reveal the space negotiations of santri in maintaining socio-religious identity at the Wonosobo Al-Qur'an Science University, where the research locus that has been conducted has not specifically found this matter. This article is field research, using qualitative methods, where the data collected and analyzed are in the form of words and images which can be used as material for logical and systematic interpretation so that conclusions can be drawn from these data. Data collection used interview, observation and documentation techniques. The results of the research show: that the Wonosobo santri who study at the Al-Qur'an Science University still maintain their identity in the form of socio-religious symbols as a process of negotiating space to show that an area or symbol is a form of symbolic power displayed by the santri, including in the form of wearing a skullcap in lectures as a form of student identity. Therefore, it can be understood that it is very difficult for every community not to emphasize symbols and identities displayed in public spaces or private spaces as a form of defending and controlling areas over which they have power or responsibility. The implication of the research is the need to maintain religious identity in daily activities as a safety valve in behavior and actions that reflect the morals of students.